(untitled) (The Review of Diabetic Studies, 2025)
Nurses play a pivotal role in safeguarding patient safety within modern healthcare systems. This comprehensive review examines nurses’ multifaceted contributions to patient safety, including direct patient monitoring, error detection and prevention, communication and advocacy, education, and interdisciplinary collaboration. The evidence highlights nurses’ unique position to identify risks, prevent adverse events, and drive safety improvements due to their continuous patient contact and clinical expertise. However, various barriers, such as inadequate staffing ratios, high workload, burnout, limited resources, and hierarchical power dynamics, impede nurses’ ability to fulfill their safety responsibilities effectively. The expanding roles of specialized nurses in infection control, wound care, telehealth, and safety leadership exemplify the value of advanced nursing practice in promoting safety culture and improving patient outcomes. Nonetheless, the review reveals a persistent gap between theoretical safety education and its practical application, emphasizing the need for enhanced training in advocacy, assertiveness, and systems thinking. As healthcare systems evolve with technological advancements and increasing complexity, nurses’ roles in patient safety continue to expand, necessitating ongoing investment in their professional development, empowerment, and inclusion in organizational decision-making. Addressing systemic barriers and strengthening nurses’ capacity to lead safety initiatives is crucial for healthcare organizations striving to create a robust culture of safety and deliver high-quality, patient-centered care.